Функціональна декомпозиція просторових бізнес-екосистем - Бистряков, І.К.; Клиновий, Д.В. (Економіка природокористування і сталий розвиток, 2019)
Метою статті є функціональна декомпозиція основних стадій алгоритму забезпечення стратегічного управління розвитком бізнес-екосистеми. Визначено, що він включає оцінку ресурсного потенціалу території; визначення її ключових компетенцій; локомотивних виробництв, галузей і сфер господарювання; створення драйверів розвитку просторових систем; формування точок і зон економічного зростання; міжгалузевий перерозподіл інвестиційних потоків, внутрішнє збалансування розвитку територій; створення системи сталих фінансів і забезпечення загальносистемної сталості розвитку територіального утворення. Запропоновано відповідну схему послідовної декомпозиції бізнес-екосистеми. The purpose of the article is functional decomposition of the main stages of the algorithm of providing strategic management of business ecosystem development. It is determined that it includes the assessment of the resource potential of the territory; defining its core competencies; locomotive industries, industries and spheres of management; creation of drivers of development of spatial systems; formation of points and zones of economic growth; cross-sectoral redistribution of investment flows, internal balancing of territorial development; creating a system of sustainable finance and ensuring system-wide sustainability of territorial formation. An appropriate scheme of sequential decomposition of the business ecosystem is proposed. The functional role of the natural resource space as a source of production, raw material, energy resources and the basis for the organization of business ecosystems have been determined here. The role of key competences for the functioning of a sustainable competitive economy has been determined also. The leading role of economic drivers and locomotive industries, which are able to build powerful chains of production, supply and sale in ensuring the sustainable development of business ecosystems, has been established. Also there is established the need to create growth points as spatially-localized territorial-economic entities, wich are provided with the necessary growth drivers and focused on the production of locomotive industries. The functional role of the sustainable finance system in the extraction, redistribution, accumulation and capitalization of rental income from environmental management is characterized.